HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KOORDINASI MATA-KAKI TERHADAP KETEPATAN PASSING FUTSAL PADA EKSTRAKURIKULER DI SMP MUHAMMADIYAH TELUK KIJING - Muhsana El Cintami Lanos; Zaki Arif Rahmatullah; Bambang Hermansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the relationship between leg muscle strength and eye–foot coordination on the accuracy of futsal passing among extracurricular students at SMP Muhammadiyah Teluk Kijing. Passing accuracy is a fundamental skill that greatly determines the effectiveness of futsal matches; therefore, it needs to be supported by optimal physical condition and coordination abilities. This study used a quantitative correlational method. The sampling technique employed was saturated sampling, in which all students participating in the futsal extracurricular activity were included, totaling 30 students. Data were collected through tests of leg muscle strength, eye–foot coordination tests, and futsal passing accuracy tests, then analyzed to determine the level of relationships among the variables. The results showed that there was a significant relationship between leg muscle strength and futsal passing accuracy. In addition, eye–foot coordination also had a significant relationship with passing accuracy. Simultaneously, leg muscle strength and eye–foot coordination together were significantly related to futsal passing accuracy. This indicates that passing accuracy is not only determined by technical training, but also by the development of leg muscle strength and eye–foot coordination in an integrated manner